2015
DOI: 10.1039/c5ta00127g
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical performance of α-MoO3–In2O3 core–shell nanorods as anode materials for lithium-ion batteries

Abstract: α-MoO3–In2O3 core–shell nanorods have been synthesized by a hydrothermal method. As anodes of LIBs, they exhibit excellent lithium storage performance with high reversible capacity, excellent cyclability and good rate capability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 64 publications
0
50
0
Order By: Relevance
“…[43] They also designed a-MoO 3 @MnO 2 core-shell nanorods with ac apacity of 1475 mA hg À1 at 0.1 C. [44] The capacity can be kept at 1127 mA hg À1 after 50 cycles, whichissuperior to that of the bare MoO 3 and pristine MnO 2 electrodes. By combining the physical and electrochemical properties of variousm aterials and making use of their respective merits to offset the imperfection of others, many hybrid MoO 3 -based electrodes have been fabricated with improved electrochemical properties.…”
Section: Moomentioning
confidence: 99%
See 1 more Smart Citation
“…[43] They also designed a-MoO 3 @MnO 2 core-shell nanorods with ac apacity of 1475 mA hg À1 at 0.1 C. [44] The capacity can be kept at 1127 mA hg À1 after 50 cycles, whichissuperior to that of the bare MoO 3 and pristine MnO 2 electrodes. By combining the physical and electrochemical properties of variousm aterials and making use of their respective merits to offset the imperfection of others, many hybrid MoO 3 -based electrodes have been fabricated with improved electrochemical properties.…”
Section: Moomentioning
confidence: 99%
“…Xue and co-workersr eported composite a-MoO 3 /In 2 O 3 core-shell nanorods, which delivered ah igh reversible capacity of 1304 mA hg À1 at 0.2 C, ah igh capacity retention of 1114mAhg À1 after 50 charge/discharge cycles, and superior rate capability. [43] They also designed a-MoO 3 @MnO 2 core-shell nanorods with ac apacity of 1475 mA hg À1 at 0.1 C. [44] The capacity can be kept at 1127 mA hg À1 after 50 cycles, whichissuperior to that of the bare MoO 3 and pristine MnO 2 electrodes. Such excellent electrochemical properties can be ascribed to the synergistic effect of the short lithium-ion diffusion pathway and interfacial spaces between the core and shell components.…”
Section: Moomentioning
confidence: 99%
“…3D porous, 16 and hollow spheres, 17 1D nanotubes, 18 35 In addition, considerable efforts have been focused on the electrode materials with coreshell structures, which can deliver superior cycling performance and rate properties. [36][37][38] Therefore, the preparation of core-shell nanostructured titanium 75 dioxide electrode materials is a valid method to improve the performance in LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been confirmed that the electrochemical performance is strongly related to the electrical conductivity of the electrodes. In this regard, different conductive materials, such as conductive polymer [17], graphene [18][19][20], amorphous carbon [21][22][23], carbon nanotubes [24] and In 2 O 3 [8] have been used for incorporating MoO 3 within the electrode base material.…”
Section: Introductionmentioning
confidence: 99%
“…Sn [2], Si [3] and Ge [4]), and conversion-type (e.g. Co 3 O 4 [5], V 2 O 5 [6], Fe 2 O 3 [7] and MoO 3 [8]). Although graphite has been extensively employed as anode material in commercial LIBs for many years, its relatively low Li ion storage capacity (theoretical capacity of 372 mAh/g) restricts the further improvement of LIBs.…”
Section: Introductionmentioning
confidence: 99%